Inculcating Religious Moderation Values to Counter Radicalism in Islamic Junior Secondary School Students - Zainal Abidin; Rizha Ulfatul Fitriana (Edukasia Islamika, 2021)
Some experts believe that students are considered to be a distinctive target for radical groups’ mobilization, especially for those who are enrolled for Rohis activities at schools. This is in line with some survey result revealing that the rampant radicalism among students has increased. Unfortunately, studies on radicalism prevention tend to be more theoretical and focusing more on MA / SMA / SMK students. This study aims to reveal the rationale behind the radicalism prevention which includes some various efforts to prevent radicalism, and the results accomplished from such effort in Madrasah Tsanawiyah (MTs) students. This is significantly important because MTs students are in their early adolescence phase that is unstable, imitative, and aggressive which makes them vulnerable for being exposed to radicalism. This study utilizes a qualitative approach. The data were collected through interviews, observations, and documentation, which were then, analyzed using the interactive models of Miles, Huberman, and Saldana which consisted of condensation, presentation, and verification. This study suggested that radicalism prevention was driven by the deep concern of principals and teachers of Madrasah over the rise of students who are exposed to radicalism. Madrasahs are seen to be seriously giving vaccines to students so that they are immune from the radicalism virus. The vaccine is internalized systemically and continuously involving the process of strengthening nationalism in daily routine and extracurricular activities, strengthening the counter-radicalization through the subject of PAI and PPKn, and developing the Aswaja-NU based curriculum. The vaccine is at a certain level capable of establishing students’ religious moderation values ​​as well as it can strengthen their immunity from the confrontation of the radicalism virus. Student immunity, of course, is not interminable for the conflict between vaccines and viruses is timeless so that Madrasah must always continuously update the types of vaccines and the internalization methods.